2022
DOI: 10.1038/s41598-022-11447-7
|View full text |Cite
|
Sign up to set email alerts
|

Actions of CSF2 and DKK1 on bovine embryo development and pregnancy outcomes are affected by composition of embryo culture medium

Abstract: Procedures for in vitro embryo production in cattle have not been optimized. In the current experiment, we utilized a 3 × 3 factorial design to test whether the proportion of embryos becoming blastocysts in culture and the pregnancy rate after embryo transfer are affected by type of serum in the medium [no serum; 3% (v/v) KnockOut Serum Replacement (SR); 3% (v/v) fetal bovine serum (FBS)] and addition of specific embryokines [vehicle; 10 ng/mL colony stimulating factor 2 (CSF2); 100 ng/mL dickkopf related prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Because determinants of pregnancy success are multifactorial, some studies have not observed benefits of treating embryos during culture or, in some cases, the embryo culture system and media composition affected pregnancy outcomes. For example, Amaral et al (2022) observed a positive effect on development to the blastocyst stage in embryos exposed to serum or serum replacer during culture, but a lower pregnancy rate after the transfer of these embryos into recipients. Moreover, if CSF2 or DKK1 were added to culture medium, actions of theses embryokines were dependent on the presence of serum in the medium.…”
Section: Signaling Molecules To Mimic Maternal Reproductive Tractmentioning
confidence: 99%
“…Because determinants of pregnancy success are multifactorial, some studies have not observed benefits of treating embryos during culture or, in some cases, the embryo culture system and media composition affected pregnancy outcomes. For example, Amaral et al (2022) observed a positive effect on development to the blastocyst stage in embryos exposed to serum or serum replacer during culture, but a lower pregnancy rate after the transfer of these embryos into recipients. Moreover, if CSF2 or DKK1 were added to culture medium, actions of theses embryokines were dependent on the presence of serum in the medium.…”
Section: Signaling Molecules To Mimic Maternal Reproductive Tractmentioning
confidence: 99%
“…Efforts to enhance blastocyst yield by modifying embryo culture media have been less successful. Addition of serum to culture medium can have a large positive effect on development to the blastocyst stage but may also reduce competence of the resultant embryos to establish pregnancy ( Amaral et al, 2022 ). The percent of embryos becoming blastocysts can also be increased by addition to embryo culture medium of oviductal fluid ( Lopera-Vasquez et al, 2017 ) and specific embryokines produced by the reproductive tract ( Wooldridge et al, 2022 ) but the magnitude of effects is small.…”
Section: Increasing the Yield Of Transferrable Embryosmentioning
confidence: 99%
“…Initial experiments with two embryokines, colony-stimulating factor 2 ( CSF2 ) and dickkopf WNT signaling inhibitor 1, indicated that the addition of either molecule to embryo culture medium increased pregnancy rate after embryo transfer ( Loureiro et al, 2009 ; Denicol et al, 2014 ). More recently, however, the beneficial effects of these molecules were not observed ( Estrada-Cortés et al, 2021b ; Amaral et al, 2022 ). Actions of these or other embryokines may depend on the specific characteristics of the embryo or recipient, as some results indicate ( Dobbs et al, 2014 ; Amaral et al, 2022 ).…”
Section: Modifying Embryo Culture Conditions To Increase the Competen...mentioning
confidence: 99%
“…Treatment with CSF2 decreased embryo length and accumulation of interferon tau in the uterus in female embryos but increased both measurements in male embryos (Dobbs et al 2014). There have also been reports that blastocysts derived in the presence of CSF2 have increased competence to establish pregnancy after transfer to females, as reported in mouse (Sjöblom et al 2005), human (Ziebe et al 2013;Okabe-Kinoshita et al 2022) and cattle (Loureiro et al, 2009;Denicol et al, 2014), although contradicting reports exist on this effect of CSF2 (Zhou et al, 2016;Tribulo et al 2017;Estrada-Cortes et al 2021;Amaral et al 2022). There are reports that CSF2 influences fetal and postnatal programming when introduced during the preimplantation period in the mouse (Sjöblom et al 2005) and bovine (Kannampuzha-Francis et al 2015;Siqueira et al 2017;Estrada-Cortés et al 2021).…”
Section: Introductionmentioning
confidence: 95%